Successful Treatment of Iatrogenic Vertebral Pseudoaneurysm Using Pipeline Embolization Device - Sudheer Ambekar (Case Reports in Vascular Medicine, 2014)
Traumatic pseudoaneurysms are uncommon and one of the most difficult lesions to treat. Traditional treatment methods have focused on parent vessel sacrifice with or without revascularization. We report the case of a patient who underwent successful treatment of an iatrogenic extracranial vertebral artery pseudoaneurysm using the Pipeline Embolization Device. A 47-year-old man sustained an inadvertent injury to the left vertebral artery during C1-C2 fixation. Subsequent imaging revealed an iatrogenic vertebral artery pseudoaneurysm. Immediate angiogram was normal. A repeat angiogram done after 3 days of the surgery revealed a vertebral artery pseudoaneurysm. He underwent aneurysm exclusion and vascular reconstruction using the Pipeline Embolization Device. Although flow-diverting stents are currently not being used for treating traumatic pseudoaneurysms, their use may be considered in such cases if active bleeding has ceased. In our case, the patient did well and the aneurysm was excluded from circulation while reconstructing the vessel wall.